Nitroxide-Mediated Radical Ring-Opening Copolymerization: Chain-End Investigation and Block Copolymer Synthesis - Delplace, Vianney; Harrisson, Simon; Tardy, Antoine; Gigmes, Didier; Guillaneuf, Yohann; Nicolas, Julien (Macromolecular rapid communications., 2014)
Well‐defined, degradable copolymers are successfully prepared by nitroxide‐mediated radical ring opening polymerization (NMrROP) of oligo(ethylene glycol) methyl ether methacrylate (OEGMA) or methyl methacrylate (MMA), a small amount of acrylonitrile (AN) and cyclic ketene acetals (CKAs) of different structures. Phosphorous nuclear magnetic resonance allows in‐depth chain‐end characterization and gives crucial insights into the nature of the copolymer terminal sequences and the living chain fractions. By using a small library of P(OEGMA‐co‐AN‐co‐CKA) and P(MMA‐co‐AN‐co‐CKA) as macroinitiators, chain extensions with styrene are performed to furnish (amphiphilic) block copolymers comprising a degradable segment. Degradable block copolymers are successfully prepared by nitroxide‐mediated radical ring‐opening polymerization and characterized by phosphorous nuclear magnetic resonance, allowing the nature of the copolymer terminal sequences to be elucidated and the living chain fractions to be calculated. The synthesis of block copolymers comprising a degradable block is also reported.